Universiti Kebangsaan Malaysia Library library generates a knowledge society - Universiti Kebangsaan Malaysia (Bangi : Perpustakaan Universiti Kebangsaan Malaysia, 2006)
Video corporate of Universiti Kebangsaan Malaysia library includes their services, facilities, rules and collection
English version
Keywords: Documentary films